Reflexive methodology : new vistas for qualitative research - Alvesson, Mats (SAGE, 2009)
Praise for the First Edition: 'Reflexive Methodology is a textbook indispensable to any young researcher. It does not tell its readers how to do research. It does something much more important: It shows how research has been done in the qualitative tradition, thus encouraging the readers to make their own choices' - Barbara Czarniawska, Goteborg University 'I would go so far as to argue that this book should be on the reading list of all social scientists and philosophers with an interest in the theory and practice of research' - Prometheus Reflexive Methodology established itself as a groundbreaking success, providing researchers with an invaluable guide to a central problem in research methodology - how to put field research and interpretations in perspective, paying attention to the interpretive, political and rhetorical nature of empirical research. Now thoroughly updated, the Second Edition includes a new chapter on positivism, social constructionism and critical realism, and offers new conclusions on the applications of methodology. It also provides further illustrations and updates that build on the acclaimed and successful first edition. Reflexivity is an essential part of the research process. In this book, Mats Alvesson and Kaj Skoldberg make explicit the links between techniques used in empirical research and different research traditions, giving a theoretically informed approach to qualitative research. The authors provide balanced reviews and critiques of the major schools of grounded theory, ethnography, hermeneutics, critical theory, postmodernism and poststructuralism, discourse analysis, genealogy and feminism. This book points the way to a more open-minded, creative interaction between theoretical frameworks and empirical research. It continues to be essential reading for students and researchers across the social sciences.